Pengaruh Penerapan Etika Pemasaran Islami Terhadap Kepuasan Pelanggan (Studi Pada Pelanggan Produk Chiztikk Surabaya) - Melania, Farah Avista; Ridlwan, Ahmad Ajib (Jurnal Iqtisaduna, 2022)
Rasulullah SAW was a successful businessman in his time. He applies key success factors that make his business grow rapidly and get blessings on the side of Allah SWT, and avoid danger and cheating which is prohibited in Islam. As a Muslim business actor, you should be able to carry out the rules of buying and selling in accordance with Islamic law like the Prophet SAW. This study aims to identify the effect of applying Islamic marketing ethics on customer satisfaction for Chiztikk Surabaya products by using simple linear regression. This method is used to test the effect of variables with quantitative analysis. Questionnaires were distributed via google forms to respondents who were selected using a purposive sampling technique by determining the number of samples using the cochran formula. Respondents’ answers were measured using a Likert scale. This study shows that Islamic marketing ethics as an independent variable has an influence on customer satisfaction as the dependent variable of 59.5% (R2). This study provides managerial implications for producers or sellers, where the application of Islamic marketing ethics is very important to achieve customer satisfaction.